Strategic Approaches: Interlocutory Methods for Fostering Harmony in the Conflict Landscapes of Somalia and Sudan - Abdiweli Hussein; Reginald Nalugala (Eastern African Journal of Humanities and Social Sciences)
This study examined how integrating grand strategy with interlocutory methods could address ongoing conflicts in Somalia and Sudan. It explored combining high-level frameworks with localised peacebuilding efforts, such as community dialogue and grassroots participation, to promote lasting stability. Using qualitative methods—case studies, stakeholder interviews, and policy reviews—the research assessed traditional conflict resolution approaches and highlighted gaps. Findings showed that military and diplomatic strategies alone were insufficient, while local, inclusive methods offered greater promise. The study concluded that sustainable peace requires aligning international and regional strategies with local realities. It recommended enhancing multilateral cooperation, strengthening local engagement, and tailoring grand strategies to the unique dynamics of each conflict area.